Ionization of Surfactants at the Air/Water Interface - Phan, Chi (Elsevier, 2018)
Some surfactants, or surface-active agents, undergo ionization in water. The degree of ionization can affect molecular hydrophilicity and therefore the overall adsorption of surfactants at liquid surfaces. For weak ionic surfactants, such as carboxylic acids and alkylphenols, partial ionization occurs in both the bulk and near the surface. For common surfactants, including sodium dodecyl sulfate and cetyltrimethylammonium bromide, partial ionization is significant only near the surface. While partial ionization has been acknowledged in the literature, the ionization process is not fully understood. Due to the varied hydrophilicity of different ionic states, the problems of surfactant adsorption and ionization must be solved simultaneously. Partial ionization requires a comprehensive formulation rather than the simplified Gibbs equation (Rosen and Kunjappu, 2012), which is applicable only to the full dissociation. This chapter presents experimental verification, theoretical development, and molecular simulations for partial ionization of surfactants at the air–water interface. The ramifications in theoretical development and application are also discussed.